A Brief to the Commission for the Estates General on Education from Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1995)
One of the stated aims of the Home and School movement is to assist in forming public opinion favourable to educational reform and to the advancement of the education of the child. Thus we are pleased to be able to submit this brief to the Commission for the Estates General on Education. This brief is presented in both French and English. However, these two versions are not direct translations, but have been written independently based on the same input and the same discussions. Care has been taken to examine both versions to ensure that their message is the same.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)
Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)
Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)
Number of pages: 16